Predictive factors for a severe course of COVID-19 infection in myasthenia gravis patients with an overall impact on myasthenic outcome status and survival - Jakubíková, Michala; Týblová, Michaela; Tesař, Adam; Horáková, Magda; Vlažná, Daniela; Ryšánková, Irena; Nováková, Iveta; Dolečková, Kristýna; Dušek, Pavel; Piťha, Jiří; Voháňka, Stanislav; Bednařík, Josef (European journal of neurology, 2021)
BACKGROUND AND PURPOSE: Myasthenia gravis (MG) patients could be a vulnerable group in the pandemic era of coronavirus 2019 (COVID-19) mainly due to respiratory muscle weakness, older age and long-term immunosuppressive treatment. We aimed to define factors predicting the severity of COVID-19 in MG patients and risk of MG exacerbation during COVID-19. METHODS: We evaluated clinical features and outcomes after COVID-19 in 93 MG patients. RESULTS: Thirty-five patients (38%) had severe pneumonia and we recorded 10 deaths (11%) due to COVID-19. Higher forced vital capacity (FVC) values tested before COVID-19 were shown to be protective against severe infection (95% CI 0.934-0.98) as well as good control of MG measured by the quantified myasthenia gravis score (95% CI 1.047-1.232). Long-term chronic corticosteroid treatment worsened the course of COVID-19 in MG patients (95% CI 1.784-111.43) and this impact was positively associated with dosage (p = 0.005). Treatment using azathioprine (95% CI 0.448-2.935), mycophenolate mofetil (95% CI 0.91-12.515) and ciclosporin (95% CI 0.029-2.212) did not influence the course of COVID-19. MG patients treated with rituximab had a high risk of death caused by COVID-19 (95% CI 3.216-383.971). Exacerbation of MG during infection was relatively rare (15%) and was not caused by remdesivir, convalescent plasma or favipiravir (95% CI 0.885-10.87). CONCLUSIONS: As the most important predictors of severe COVID-19 in MG patients we identified unsatisfied condition of MG with lower FVC, previous long-term corticosteroid treatment especially in higher doses, older age, the presence of cancer, and recent rituximab treatment.
Keywords: immunosuppression; Coronavirus Infections; lidé; senioři; SARS-CoV-2; Aged; Immunization, Passive; sérologická léčba covidu-19; Myasthenia Gravis; corticosteroids; koronavirové infekce; rituximab; COVID-19; myasthenia gravis; COVID-19 Serotherapy; pasivní imunizace; Humans